Synthesis and properties of Cu- and Pd-complexes of cyclen conjugates with pheophorbide and bacteriopheophorbide - A. S. Smirnov; M. A. Grin; A. F. Mironov (Тонкие химические технологии)
Objectives. Chlorin and bacteriochlorin photosensitizers are effective agents for cancer photodynamic therapy and fluorescence imaging. They are also excellent chelators forming stable metal complexes. Besides, 64Cu and 109Pd isotopes can serve as emitters for nuclear medicine. Chelation of these metals with cyclen conjugates with chlorin and bacteriochlorin photosensitizers can become a simple and universal strategy for the synthesis of diagnostic and therapeutic radiopharmaceuticals for nuclear medicine. This article reports on the synthesis of similar Cu and Pd complexes of cyclen conjugates with pheophorbide and bacteriopheophorbide and the study of their photophysical properties.Methods. Metalation of cyclen conjugates was carried out with palladium and copper acetates. For bacteriochlorins, 6-O-palmitoyl-L-ascorbic acid was additionally used as a reducing agent. MALDI mass spectrometry, which was carried out on a time-of-flight mass spectrometer Bruker Ultraflex TPF/TOF and a Bruker Daltonics Autoflex II confirmed the structure of the compounds obtained Electronic absorption spectra were obtained on a Shimadzu 3101 spectrophotometer. Fluorescence and phosphorescence spectra were obtained on a FluoTime 300 PicoQuant spectrofluorometer.Results. Photophysical studies of metal complexes showed that the introduction of palladium cations quenches fluorescence and increases the quantum yield of singlet oxygen generation to 0.98 for the chlorin conjugate. Besides, it decreases the quantum yield of fluorescence to 0.10 and increases the quantum yield of singlet oxygen generation to 0.72 for the bacteriochlorin conjugate. Introducing a copper cation to cyclen conjugates with pheophorbide and bacteriopheophorbide leads to photophysical characteristics quenching.Conclusions. Due to the stability of the synthesized metal complexes in acidic media, as well as the short metalation time (5, 20, 10, and 15 minutes) it is reasonable to expect the successful development of effective imaging agents for positron emission tomography and radionuclide therapy. In addition, the residual fluorescence of bacteriochlorins makes it possible to use fluorescence diagnostics in combination with these methods.